Transcriptome analysis reveals the high temperature induced damage is a significant factor affecting the osmotic function of gill tissue in Siberian sturgeon (Acipenser baerii) - Shiyong Yang; Datian Li; Langkun Feng; Chaoyang Zhang; Dandan Xi; Hongli Liu; Chaozhan Yan; Zihan Xu; Yujie Zhang; Yunkun Li; Taiming Yan; Zhi He; et al. (BMC Genomics, 2023)
Abstract Background Maintaining osmotic equilibrium plays an important role in the survival of cold-water fishes. Heat stress has been proven to reduce the activity of Na+/K+-ATPase in the gill tissue, leading to destruction of the osmotic equilibrium. However, the mechanism of megatemperature affecting gill osmoregulation has not been fully elucidated. Results In this study, Siberian sturgeon (Acipenser baerii) was used to analyze histopathological change, plasma ion level, and transcriptome of gill tissue subjected to 20℃, 24℃and 28℃. The results showed that ROS level and damage were increased in gill tissue with the increasing of heat stress temperature. Plasma Cl− level at 28℃ was distinctly lower than that at 20℃ and 24℃, while no significant difference was found in Na+ and K+ ion levels among different groups. Transcriptome analysis displayed that osmoregulation-, DNA-repair- and apoptosis-related terms or pathways were enriched in GO and KEGG analysis. Moreover, 194 osmoregulation-related genes were identified. Amongst, the expression of genes limiting ion outflow, occluding (OCLN), and ion absorption, solute carrier family 4, member 2 (AE2) solute carrier family 9, member 3 (NHE3) chloride channel 2 (CLC-2) were increased, while Na+/K+-ATPase alpha (NKA-a) expression was decreased after heat stress. Conclusions This study reveals for the first time that the effect of heat stress on damage and osmotic regulation in gill tissue of cold-water fishes. Heat stress increases the permeability of fish’s gill tissue, and induces the gill tissue to keep ion balance through active ion absorption and passive ion outflow. Our study will contribute to research of global-warming-caused effects on cold-water fishes.